The Explosive Characteristics of the Aurora: The Electric Current Line Approach - Akasofu, Syun-Ichi (Frontiers in Astronomy and Space Sciences, 2019)
The aurora shows explosive activities a few times in 24 hours on a moderately active day. This specific phenomenon is called the auroral substorm, which consists of the growth, expansion and recovery phases; the explosive activities occur during the expansion phase. As an introduction, the explosive activities of the aurora are morphologically described first on the basis of ground-based all-sky and satellite images. In terms of theoretical understanding, the processes for the explosive activities have been considered almost exclusively in terms of “the magnetic field line approach” in the past, including the process of magnetic reconnection. Instead, in this paper, we consider the processes in terms of “the electric current line approach”. This approach requires that the whole process of auroral substorms should be considered as a chain of processes, which consists of power supply (dynamo), transmission (currents/circuits) and dissipation (auroral substorms). An increased power of the solar wind-magnetosphere dynamo (≈ 5x1018 erg/s or 1011w) intensifies the electric currents mainly in the main body (just outside of the ring current) of the magnetosphere, resulting in accumulating energy in its inductive circuit and inflation of the magnetosphere. When the accumulated energy reaches about 5x1022 ergs (5x1015 J), the magnetosphere tends to become unstable (because of current instabilities). As the current intensity is reduced as a result, the magnetosphere is deflated. It is suggested that it is in this deflation process, during which the accumulated energy is unloaded, and an earthward electric field (5-50 mV/m) is produced on the equatorial plane, establishing the current system (the UL current system), which is responsible for the expansion phase, including the most characteristic features of the expansion phase, such as the poleward advance of the aurora and the development of the auroral electrojet. The electric current approach is rather new and needs much more effort to develop.